Developing self-assessment instruments to measure students’ performance characters in making dresses using a high order thinking skills approach - Emy Budiastuti; Sugiyem Sugiyem; Farah Najwa Ahmad Puad (LPMPP Universitas Negeri Yogyakarta, 2023)
Self-assessment in practicum courses may develop students' characters, for example, honesty, discipline, and responsibility. Moreover, it can also improve students' initiative, critical, and creative thinking. However, assessment for practicum courses is fully conducted by lecturers without any involvement from students. This study aims to develop self-assessment instruments to assess students’ characters while performing fashion design practicums using the HOTS approach. The instruments were developed using the 4D model by Thiagarajan. The model consists of some stages, namely Define, Design, Develop, and Disseminate. The sample was collected from 15 students taking the Haute Couture course. The participants of this study were selected using purposive sampling. The developed instruments were validated by experts and were considered “Almost Perfect”. The inter-rater reliability index is higher than 0.7, so it indicates that the instruments met the criteria required. Some experts in fashion design were involved to validate the instruments. The collected data were then analyzed using descriptive statistics. Based on the self-assessment, it was found that 14 out of 15 students were considered competent or having very good performances. The developed instruments can be used to assess students’ performance characters in practicum courses as they may measure students' competency (hard skill) and characters (soft skill). This study reveals that self-assessment of work attitudes needs to be pursued during practical learning to enhance learning motivation and develop relevant competencies.